Mitochondrial genome analysis, phylogeny and divergence time evaluation of Strix aluco (Aves, Strigiformes, Strigidae) - Wang, Yeying; Zhan, Haofeng; Zhang, Yu; Long, Zhengmin; Yang, Xiaofei (Pensoft Publishers, 2023)
Background Prior research has shown that the European peninsulas were the main sources of Strix aluco colonisation of Northern Europe during the late glacial period. However, the phylogenetic relationship and the divergence time between S. aluco from Leigong Mountain Nature Reserve, Guizhou Province, China and the Strigiformes from overseas remains unclear. The mitochondrial genome structure of birds is a covalent double-chain loop structure that is highly conserved and, thus, suitable for phylogenetic analysis. This study examined the phylogenetic relationship and divergence time of Strix using the whole mitochondrial genome of S. aluco . New information In this study, the complete mitochondrial genome of Strix aluco , with a total length of 18,632 bp, is reported for the first time. A total of 37 genes were found, including 22 tRNAs, two rRNAs, 13 protein-coding genes and two non-coding control regions. Certain species of Tytoninae were used as out-group and PhyloSuite software was applied to build the ML-tree and BI-tree of Strigiformes. Finally, the divergence time tree was constructed using BEAST 2.6.7 software and the age of Miosurnia diurna fossil-bearing sediments (6.0–9.5 Ma) was set as internal correction point. The common ancestor of Strix was confirmed to have diverged during the Pleistocene (2.58–0.01 Ma). The combined action of the dramatic uplift of the Qinling Mountains in the Middle Pleistocene and the climate oscillation of the Pleistocene caused Strix divergence between the northern and southern parts of mainland China. The isolation of glacial-interglacial rotation and glacier refuge was the main reason for the divergence of Strix uralensis and S. aluco from their common ancestor during this period. This study provides a reference for the evolutionary history of S. aluco .